High-gravity-hydrolysis approach to transparent nanozirconia/silicone encapsulation materials of light emitting diodes devices for healthy lighting. (August 2019) - He, Xianglei; Tang, Ruijie; Pu, Yuan; Wang, Jie-Xin; Wang, Zhi; Wang, Dan; Chen, Jian-Feng
Abstract: The white light emitting diodes (LEDs) devices based on the use of blue chips and yttrium aluminum garnet phosphors have great potential impact on energy savings in the world. However, there has been public concern over the non-visual influences of blue light on human health. Herein, we report a high-gravity-hydrolysis approach for the synthesis of transparent nanozirconia/silicone hybrid materials, which can be used as the encapsulation of white LEDs with enhanced light extraction efficiency and reduced blue light exposure. The formation of zirconia nanoparticles on silicone chains is performed in a high-gravity rotating packed bed (RPB) reactor. The homogeneous micromixing of the reactants in the RPB enables the formation of ultrasmall zirconia nanoparticles in the silicone chains. Compared with LEDs encapsulated with commercial silicone, the white LEDs packaged by nanozirconia/silicone exhibit significant enhanced luminous flux (from 13.28 to 31.34) and decreased proportion of blue light (from 3.1% to 1.8%), resulting in low correlated color temperature (4573 K). This work demonstrates a scalable and efficient approach for healthy lighting based on the commercial white LEDs technology. Graphical abstract: Image 1 Highlights: High-gravity-hydrolysis approach for scalable synthesis of nanozirconia/silicone. The luminous flux of LEDs was enhanced from 13 to 31 by nanozirconia doping. Proportion of blue light from the LEDs was decreased from 3.1% to 1.8%.